(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of emotional intelligence and servant leadership on employee performance with employee engagement as an intervening variable at the General Bureau of the East Java Provincial Secretariat. The background of this study stems from the phenomenon of fluctuations in the performance of civil servants (Aparatur sipil negara), high levels of disciplinary violations, and the need to improve the quality of public services, which requires a humanistic leadership approach and the strengthening of employees’ emotional competencies. This research is quantitative in nature with an explanatory design. The research population consists of all 108 employees of the General Bureau of the East Java Provincial Secretariat, all of whom were sampled using the total sampling method. Data were collected using a Likert scale questionnaire and then analyzed using the Partial Least Squares-based Structural Equation Modeling (SEM) technique with SmartPLS 3.0 software. The results of the study show that: (1) Emotional intelligence has a positive and significant effect on employee engagement and employee performance; (2) Servant leadership has a positive and significant effect on employee engagement and employee performance; (3) Employee engagement has a significant positive effect on employee performance; (4) Employee engagement partially mediates the effect of emotional intelligence and servant leadership on employee performance. The implications of this study confirm that increasing employee emotional intelligence and implementing a servant leadership style can strengthen employee commitment to their work and directly improve organizational performance. The results of this study are expected to provide strategic input for the East Java Provincial Government in developing more effective human resource management policies that are oriented towards public service and based on the values of empathy, integrity, and participation.